Integrated Primary Care Implementation and Patient Satisfaction - Melki Saudila; Asriwati Asriwati; Ismail Efendy (Newinera Publisher, 2026)
Integrated Primary Health Care (IPHC) aims to improve the quality, continuity, and responsiveness of primary health services. However, its implementation in Kupang City still faces challenges, as reflected in the 2023 Minimum Service Standards achievement of 82.17%, which was lower than the East Nusa Tenggara provincial average of 95.37%. This study aimed to analyze the association between IPHC-based service quality and patient satisfaction at Sikumana Public Health Center and to identify the service quality dimension with the strongest practical tendency. This study employed a quantitative explanatory design with a cross-sectional approach. A total of 100 respondents were selected using proportional stratified random sampling from six service areas. Service quality was measured using five SERVQUAL/RATER dimensions: reliability, assurance, tangibles, empathy, and responsiveness, while patient satisfaction was dichotomized for binary logistic regression analysis. Data were analyzed using univariate analysis, Chi-Square tests, and binary logistic regression. The bivariate analysis showed that only reliability was significantly associated with patient satisfaction. However, in the multivariate analysis, none of the five service quality dimensions showed a statistically significant partial effect after simultaneous analysis. The regression model was statistically significant, showed good model fit, and explained 31.7% of the variation in patient satisfaction. Tangibles had the highest odds ratio, indicating the strongest practical tendency in shaping patient satisfaction. These findings suggest that patient satisfaction in IPHC implementation is multidimensional, with physical facilities, equipment adequacy, cleanliness, and service readiness requiring practical attention.